A Permeable Succinate Improved Platelet Mitochondrial Respiration in Paediatric Acute Lymphoblastic Leukaemia in Remission – Case Report: Permeable succinate improved platelet respiration in pediatric leukemia - Lelcu, Theia; Bina, Anca-Mihaela; Avram, Vlad-Florian; Arghirescu, Smaranda; BOrza, Claudia; MUNTEAN, Danina-Mirela (Scripta Medica, 2022)
Acute lymphoblastic leukaemia (ALL) is the most common childhood malignancy. In the last decades, the survival rate of paediatric patients diagnosed with ALL has been significantly improved due to standardised treatment protocols based on risk stratification. Platelet mitochondrial dysfunction has been recently reported to occur in most chronic diseases, including malignancies. Permeable succinate (NV118) is a novel mitochondria-targeted compound capable to alleviate disease and drug-induced mitochondrial dysfunction. It is reported here that ex vivo incubation with NV811 elicited an increase in platelet mitochondrial respiration in a paediatric patient with acute lymphoblastic leukaemia in remission.